1993
DOI: 10.1007/bf00146270
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between degree of histological gastritis and DNA fingerprints, cytotoxicity and adhesivity of Helicobacter pylori from different gastric sites

Abstract: Thirty-six isolates of H. pylori from up to three gastric biopsy sites (antrum, corpus and fundus) from 13 patients in Italy with different degrees of histological gastritis were investigated. All strains were tested for motility, cytotoxicity and degree of adhesion, and were typed by analysis of ribosomal RNA gene patterns (ribopatterns). Seventeen different DNA types (ribotypes) were identified, with each patient possessing H. pylori of one or more unique types. Only two patients had identical H. pylori at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
3
20
0
Order By: Relevance
“…To avoid the possibility of our results being skewed by differences in culture efficiency of pooled cagA + and cag A− strains, we tested for cag A in several well separated colonies from primary plates per patient. Our results, showing that two thirds of patients harboured both cag A+ and cag A− organisms, are compatible with those obtained by van der Ende et al 16on members of a single family (four of seven members harboured cag A+ and cag A− colonies), and are supported by an earlier study on genomic variety of H pylori strains isolated from different gastric sites of the same patients, a study that showed that 85% of 13 Italian patients were colonised by strains with different ribotypes 18. The latter study, however, also suggests that cag A+ and cag A− organisms from the same patient may be different strains 18.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To avoid the possibility of our results being skewed by differences in culture efficiency of pooled cagA + and cag A− strains, we tested for cag A in several well separated colonies from primary plates per patient. Our results, showing that two thirds of patients harboured both cag A+ and cag A− organisms, are compatible with those obtained by van der Ende et al 16on members of a single family (four of seven members harboured cag A+ and cag A− colonies), and are supported by an earlier study on genomic variety of H pylori strains isolated from different gastric sites of the same patients, a study that showed that 85% of 13 Italian patients were colonised by strains with different ribotypes 18. The latter study, however, also suggests that cag A+ and cag A− organisms from the same patient may be different strains 18.…”
Section: Discussionsupporting
confidence: 89%
“…However, seropositivity for VacA and CagA does not determine the composition of the bacterial population in the stomach, and the characteristics of a single clone cannot be extrapolated to all the helicobacters colonising the same organ. As there is evidence that bacterial phenotypic variety and genomic macro- or micro-diversity can exist within the stomach of a single patient,11 18 23 it was important to determine whether strains with different expression of cag A could colonise the same patients at the same time. A number of investigators have tackled this problem, but we believe that the frequency of mixed cultures that they observed was probably underestimated,9 15-18 partly because, in some cases, pooled colonies had been stored at − 70°C before the tests were carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple infections by different strains of Hel. pylori (Beji et al, 1989 ;Owen et al, 1993 ;Fujimoto et al, 1994 ;Akopyants et al, 1995 ;Taylor et al, 1995 ;, as well as localized mixed occurrences (Kitamoto et al, 1998 ;J. C. Atherton, unpublished) have been reported, but there is no evidence that these strains compete via exponential growth.…”
Section: Discussionmentioning
confidence: 99%
“…Data obtained by biotyping (28), plasmid profiling (42,55), restriction fragment length polymorphism analysis of genomic DNA (1,26,30,42,43,47,49,58) and specific loci (2,11,13,14,18,20,22,48,59), and repetitive extragenic palindromic PCR (REP-PCR) (23) have shown that there are substantial levels of variation among natural isolates of this pathogen. However, several important questions remain unanswered about the diversity observed among H. pylori isolates.…”
mentioning
confidence: 99%